Si-coated C / C nano composite material, preparation method thereof and high-performance lithium ion battery

Through the application of Si@C/C nanocomposites in lithium-ion batteries, the Si@C nanocomposites are distributed in the carbon frame by using the sol-gel method, which solves the problems of poor conductivity and volume changes of the negative electrode materials of lithium-ion batteries. High capacity and cycle stability are improved, and costs are reduced.

CN119297250APending Publication Date: 2025-01-10ANHUI NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411511767.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Graphite, the negative electrode material of existing lithium-ion batteries, has problems with low specific capacity and slow lithium ion diffusion rate, and low purity graphite leads to frequent side reactions during lithium ions embedded and disengagement, resulting in rapid attenuation of battery capacity.

Method used

Si@C/C nanocomposite material is used to uniformly distribute Si@C nanocomposite material in the carbon skeleton by sol-gel method, which improves conductivity and alleviates the volume changes of the silicon negative electrode during charging and discharging, and uses porous carbon skeleton Provide space to avoid structural collapse.

Benefits of technology

The cycle stability and capacity of lithium-ion batteries are significantly improved, the cost is reduced, and the electrochemical performance is enhanced through surface coating and three-dimensional framework structure, avoiding irreversible lithium ion insertion and electrode structure powderization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297250A_ABST
    Figure CN119297250A_ABST
Patent Text Reader

Abstract

According to the Si-coated C / C nano composite material, the preparation method thereof and the high-performance lithium ion battery provided by the invention, nano silicon particles and dopamine hydrochloride are used as raw materials, and an amorphous carbon layer is formed on the surface of the raw materials through preparation, so that the conductivity of a silicon negative electrode is improved; and meanwhile, surface passivation or structure collapse of the silicon negative electrode caused by excessive lithium ion embedding is prevented. And carrying out one-step carbonization through a sol-gel method to obtain the silicon-coated carbon / carbon. Compared with the prior art, the silicon-electrolyte contact area is increased, so that the electron / ion transmission kinetics is improved. In addition, the silicon and carbon nanoparticles are mostly anchored on the porous three-dimensional frame, so that the agglomeration phenomenon of the silicon particles of the nanostructure can be prevented, meanwhile, a large amount of space is provided, the violent volume change of the silicon negative electrode in the charging and discharging process is relieved, and the silicon negative electrode is prevented from falling off from the current collector. The prepared lithium ion battery has the advantages of good cycle performance, high energy density, no toxicity, no pollution and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation and lithium ion batteries, and specifically relates to a Si@C / C nanocomposite material and a preparation method thereof, and a high-performance lithium ion battery. Background Art

[0002] Currently, the negative electrode material of commercial lithium-ion batteries is mostly graphite. Using it as the negative electrode material of lithium-ion batteries often faces the problems of low specific capacity and slow lithium ion diffusion rate. In addition, low-purity graphite will cause more side reactions during the insertion and extraction of lithium ions. Therefore, finding a safe, stable, high-capacity, easy-to-purify and low-cost negative electrode has gradually become the focus of negative electrode research and development.

[0003] The next generation of lithium-ion battery negative electrodes currently reported are mainly composed of metal sulfides or oxides, graphene, alloy materials or some other embedded negative electrodes. Among them, in recent years, single silicon is expected to become the negative electrode of the next generation of lithium-ion batteries because of its high capacity, high energy density, low cost, safety and environmental protection. As the second most abundant element in the earth's crust, silicon's abundant content brings low cost and great price advantage. When single silicon is used as the negative electrode of lithium-ion batteries, it shows an extremely low embedding platform, which makes the battery made by matching the silicon negative electrode with commonly used positive electrode materials (such as lithium cobalt oxide and lithium iron phosphate) show a wide voltage window, which is beneficial to the improvement of battery energy density. When lithium ions are embedded in silicon, an alloying reaction occurs. When the silicon is completely lithiated to form Li 4.4 Si, the theoretical capacity is up to 4200mAh g -1 , which is far higher than the mainstream graphite negative electrode currently on the market.

[0004] However, silicon negative electrodes usually face the disadvantage of poor conductivity during the charge and discharge process, and the lithiation / delithiation process will cause a huge volume change of silicon, resulting in the collapse of the electrode material structure. In addition, as the charge and discharge process proceeds, a large number of lithium ions are enriched on the surface of the silicon negative electrode to form a solid electrolyte interface film (SEI), causing irreversible embedding of lithium ions, resulting in rapid capacity decay.

[0005] Therefore, it is very necessary to provide a lithium-ion battery negative electrode material with high cycle stability and not easy to collapse. Summary of the invention

[0006] The object of the present invention is to provide a Si@C / C nanocomposite material and a preparation method thereof, wherein the Si@C nanocomposite material is uniformly distributed in a carbon skeleton by a sol-gel method, and the volume change of the silicon negative electrode during the charge and discharge process is alleviated by material compounding, which is beneficial to the improvement of the conductivity of the material as a whole, and the porous carbon skeleton also provides a large amount of space for the volume expansion of silicon single substance. At the same time, the material preparation method is simple and low in cost.

[0007] Another object of the present invention is to provide a high-performance lithium-ion battery prepared using the above-mentioned Si@C / C nanocomposite material. The use of the Si@C / C nanocomposite material as the negative electrode greatly improves the conductivity of the silicon negative electrode, and the three-dimensional framework structure prepared by the sol-gel method can effectively alleviate the volume change of silicon monomer during the charging and discharging process, thereby preventing the active material from falling off the current collector. The obtained lithium-ion battery not only has a high capacity, but also has a low cost and good stability, and has a good market prospect.

[0008] The specific technical solutions of the present invention are as follows:

[0009] A method for preparing a Si@C / C nanocomposite material comprises the following steps:

[0010] 1) dispersing silicon particles in water, then adding tris(hydroxymethyl)aminomethane, hydrochloric acid and dopamine hydrochloride under stirring, stirring, centrifuging, washing and drying; and then calcining in an inert atmosphere to obtain a Si@C composite material;

[0011] 2) dispersing the Si@C composite material in water, adding acrylamide monomer and N,N-methylenebisacrylamide crosslinking agent, dissolving under stirring at room temperature, adding a photoinitiator and mixing evenly, and forming a gel by ultraviolet light irradiation;

[0012] 3) The obtained gel is immersed in liquid nitrogen and freeze-dried to obtain a precursor, which is then calcined in an inert atmosphere to obtain a Si@C / C nanocomposite material.

[0013] In step 1), the mass ratio of silicon particles to water is 1:5000 to 1:50, preferably 1:500, and the particle size of the silicon particles is 40 to 100 nm; the mass ratio of trihydroxyaminomethane to water is 1:100 to 4:5, preferably 1.2:50, and the concentration of the hydrochloric acid solution is 12 mol L -1 , the volume ratio of dopamine hydrochloride to water is 1:500 to 2:5, preferably 1:50, the pH range of the solution is adjusted to 7 to 11, preferably 8.5, the mass ratio of dopamine hydrochloride to water is 1:10000 to 1:10, preferably 1:1000; the stirring time is 0.5 to 120 hours; the inert atmosphere is argon, the calcination temperature is 300 to 800°C, and the calcination time is 0.5 to 12 hours.

[0014] In step 2), the mass ratio of the Si@C composite material to water is 1:5000 to 1:50, preferably 2:500, the mass ratio of the acrylamide monomer to water is 1:50 to 9:10, preferably 3:5, the mass ratio of the N,N-methylenebisacrylamide crosslinker to water is 1:20000 to 1:200, preferably 1:5000; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the volume ratio thereof to water is 1:5000 to 1:10, preferably 1:1000; the ultraviolet light irradiation time is 5 to 6400 s, preferably 40 s.

[0015] In step 3), the freeze-drying time is 0.5 to 96 hours; the sample is immersed in liquid nitrogen at -196°C and then frozen and dried; the inert atmosphere is argon, the calcination temperature is 300 to 800°C, and the calcination time is 0.5 to 12 hours.

[0016] The invention provides a Si@C / C nanocomposite material, which is prepared by the above method; the Si@C / C nanocomposite material is a Si@C / C nanocomposite material in which Si@C is anchored on a carbon framework, the Si@C is nano-spherical with a diameter of 40-100nm, and the carbon framework is a porous structure.

[0017] The present invention provides a high-performance lithium-ion battery, which is prepared using the above-mentioned Si@C / C nanocomposite material; the specific method is: using the Si@C / C nanocomposite material as a negative electrode material, a metal lithium sheet as a counter electrode, a porous polypropylene film as a diaphragm, and a binary electrolyte as an electrolyte to assemble a high-performance lithium-ion battery.

[0018] The preferred method for preparing a high-performance lithium-ion battery is as follows: after mixing Si@C / C nanocomposite materials with conductive carbon black and a binder evenly, the materials are dispersed in deionized water under stirring, and the slurry is obtained by stirring, and the slurry is coated on the surface of copper foil, and the negative electrode is obtained after vacuum drying; the metal lithium sheet is used as the counter electrode, the polypropylene porous film is used as the diaphragm, and the lithium salt organic solution is used as the electrolyte to assemble the lithium-ion battery. The mass ratio of Si@C / C nanocomposite materials, conductive carbon black and binder is 6:3:1, the binder is a high molecular polymer carboxymethyl cellulose (CMC), the slurry is stirred for 2 to 48 hours, the thickness of the prepared slurry coated on the surface of the copper foil is 10 to 400 μm, the drying temperature is 40 to 100 ° C, the drying time is 2 to 48 hours, and the size cut is 1.2 cm in diameter. The electrolyte is a binary electrolyte, and the solvent is a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, in which 1.0M LiPF6 is dissolved as a solute.

[0019] In the preparation method of the Si@C / C nanocomposite provided by the present invention, nano silicon particles and dopamine hydrochloride are used as raw materials, and stirred under a pH condition of 7 to 11, so that dopamine hydrochloride forms a polymer on the surface of silicon particles, and then the polydopamine is carbonized by heating in an air-tight state, and an amorphous carbon layer is formed on its surface, which is used to construct an artificial SEI film, and while improving the conductivity of silicon particles, the SEI film thickening caused by the continuous irreversible embedding of lithium ions on the surface of silicon particles is avoided, which is beneficial to the long-term cycle performance of the battery. In addition, the hydrogel prepared by acrylamide monomer and N, N-methylenebisacrylamide crosslinker contains a large amount of water, the polymer framework is evenly dispersed in the solution to form a spatial three-dimensional network structure, and water molecules are dispersed in large quantities in the cage structure formed by the framework. The prepared gel is placed in liquid nitrogen, and the extremely fast freezing characteristics of liquid nitrogen can prevent liquid from seeping out, thereby maintaining the framework structure of the gel. After the completely frozen gel is placed in a freeze dryer for sufficient drying, the water in the three-dimensional framework can be removed, thereby retaining the three-dimensional spatial network structure of the polyacrylamide polymer framework. Calcination in an argon atmosphere can remove most of the elements, thereby forming a Si@C / C nanocomposite material with a three-dimensional spatial network structure. Compared with silicon particles or Si@C, the porous structure in the Si@C / C nanocomposite material of the present invention can provide a large amount of space to alleviate the drastic volume change of silicon during the insertion and extraction of lithium ions, avoid the pulverization of the electrode structure caused by structural collapse, and greatly improve the cycle stability of the silicon negative electrode.

[0020] Compared with the prior art, the present invention has the following advantages: the amorphous carbon layer coated on the surface of the prepared Si@C nanocomposite material effectively prevents irreversible embedding of lithium ions compared to silicon particles, thereby improving the stability of silicon particles. Dispersing Si@C in porous carbon gives the material a porous characteristic, which on the one hand improves the electronic conductivity of the silicon negative electrode, and on the other hand alleviates the volume change of silicon during the charging and discharging process, thereby improving the cycle stability of the electrode. The present invention improves the electrochemical performance and cycle stability of the Si@C / C nanocomposite material by synergistically enhancing the surface coating and the three-dimensional skeleton structure. The prepared Si@C / C nanocomposite material has stable physicochemical properties, is not easy to deteriorate in the air, and is easy to store; the assembled lithium-ion battery has excellent electrochemical performance and cycle stability; and the raw materials of the present invention are low in price, the synthesis process is simple, and mass production can be carried out. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a SEM image of silicon particles in Example 1;

[0022] Figure 2 is a SEM image of the Si@C nanocomposite prepared in Example 1;

[0023] Figure 3 is the BET specific surface area of ​​the silicon particles and the prepared Si@C nanocomposite in Example 1;

[0024] Figure 4 TEM images of silicon particles and prepared Si@C nanocomposites in Example 1;

[0025] Figure 5 is the SEM image of Si@C / C prepared in Example 1;

[0026] Figure 6 XRD patterns of silicon particles, Si@C and Si@C / C nanocomposites in Example 1;

[0027] Figure 7 The electrochemical performance diagram of the high-performance lithium-ion battery assembled in Example 2;

[0028] Figure 8 is the SEM image of Si@C / C prepared in Comparative Example 2;

[0029] Fig. 9 The electrochemical performance diagram of Si@C / C prepared in Comparative Example 2;

[0030] Fig.10 is the electrochemical performance diagram of the battery in Comparative Example 3;

[0031] Fig.11 This is the electrochemical performance diagram of the battery in Comparative Example 4. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0034] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0035] Example 1

[0036] A method for preparing a Si@C / C nanocomposite material comprises the following steps:

[0037] 1) Preparation of Si@C composite material: 40 mg of spherical silicon particles with a particle size of 40 to 100 nm (the SEM image of which is shown in Figure 1 ) were ultrasonically dispersed in 20 mL of water, and then 0.48 g of tris(hydroxymethyl)aminomethane, 0.4 mL of 12 mol L -1 The hydrochloric acid solution and 20 mg of dopamine hydrochloride were added to adjust the pH range of the solution to 8.5; after continuing to stir for 24 hours, the solution was dried by centrifugal washing and calcined at 500°C for 1 hour in an argon atmosphere to obtain a Si@C nanocomposite material, as shown in its SEM image. Figure 2 As shown. Figure 3 It can be observed that after the amorphous carbon surface is coated, the BET specific surface area increases from 55.5m 2 g -1 Reduced to 32.2m 2 g -1 .from Figure 4 An amorphous carbon shell can be observed on the surface of Si particles.

[0038] 2) 80 mg of the Si@C composite material obtained in step 1) was ultrasonically dispersed in 20 mL of deionized water, 12 g of acrylamide monomer and 4 mg of N,N-methylenebisacrylamide crosslinker were added to the resulting suspension, and 20 μL of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone was added, and the acrylamide monomer was polymerized to form a gel by ultraviolet light irradiation for 40 s.

[0039] 3) The obtained gel was immersed in liquid nitrogen, and after it was completely solidified, it was placed in a freeze dryer and dried for 48 hours to obtain a loose porous precursor. -1 The Si@C / C nanocomposite material was obtained by heating the sample to 500°C at a heating rate of 100 °C and calcining the sample for 4 h. Figure 5 As shown, Si@C is anchored on the carbon framework. The loose and porous structure is conducive to the penetration of electrolyte and the transport of electrons and ions. XRD confirmed that the prepared material is silicon, where the broad peak between 20° and 30° corresponds to the large amount of carbon contained in the material.

[0040] Example 2

[0041] A high-performance lithium-ion battery is prepared using the Si@C / C nanocomposite material prepared in Example 1; the specific method is as follows:

[0042] 1) 0.7 g of the prepared Si@C / C was mixed evenly with conductive carbon black and carboxymethyl cellulose in a mass ratio of 6:3:1, and then dispersed in 1.9 g of deionized water under magnetic stirring and stirred for 24 h to obtain a slurry. The slurry was coated on the surface of a copper foil with a thickness of 150 μm, dried in a vacuum drying oven at 80°C for 16 h, and then cut into small discs with a diameter of 1.2 cm as the negative electrode.

[0043] 2) The electrode sheet obtained in step 1) is used as the negative electrode, the metal lithium sheet is used as the counter electrode, the polypropylene porous film is used as the diaphragm, and the LiPF6 binary electrolyte is used as the electrolyte. The concentration of LiPF6 is 1.0M, and the solvent is a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1 to assemble a lithium-ion battery.

[0044] 3) The lithium-ion battery obtained in step 2) was placed for 12 hours at 0.1A g -1 The charge and discharge tests were carried out at a current density of 1.5V. A wide platform at 0.2V on the discharge curve corresponds to the embedding of lithium ions into the silicon negative electrode, while a platform at 0.6V on the charge curve corresponds to the deintercalation of lithium ions. The results show that the embedding / deintercalation process of lithium ions in the silicon negative electrode is highly reversible. Among them, the coulombic efficiency of the first three cycles was less than 90%, which was attributed to the solid electrolyte interface (SEI) film generated on the surface of the Si@C / C negative electrode during the initial cycle. After 30 cycles, the battery capacity increased from 2066.8mAh g -1 Down to 1265.0mAh g -1 , with high capacity retention and charge and discharge coulombic efficiency greater than 99%.

[0045] Comparative Example 1

[0046] The same method as in Example 1 was used, except that the mass of acrylamide monomer in step 2) of Example 1 was changed to 0.3 g. Gel could not be formed under the same preparation conditions. This may be because too little monomer could not form a strong three-dimensional network structure, resulting in low mechanical properties.

[0047] Comparative Example 2

[0048] The same method as in Example 1 was used, except that the mass of the acrylamide monomer in step 2) of Example 1 was changed to 20 g, and free radical polymerization was performed under the same conditions, and then in-situ carbonization was performed under the same conditions. The SEM image of the obtained Si@C / C composite material is shown in FIG. Figure 8 As shown, the excessively high polymer content makes the interior of the gel present a dense structure. Even after carbonization, the resulting dense structure tightly wraps the internal Si@C particles, which is not conducive to electrolyte penetration and electron / ion transfer dynamics.

[0049] The Si@C / C prepared in Comparative Example 2 was assembled into a lithium-ion battery according to steps 1) to 3) in Example 2, and a charge and discharge test was performed at the same current density. The results are as follows: Fig. 9 As shown in b, the initial charge and discharge process is also accompanied by the formation of SEI film. After 30 cycles, the capacity increased from 1650.5 mAh g -1 Decay to 790.3mAh g -1 , which is attributed to the fact that excess C increases the insertion barrier of lithium ions.

[0050] Comparative Example 3

[0051] The Si@C prepared in step 1) of Example 1 was directly assembled into a lithium-ion battery according to steps 1) to 3) of Example 2, and a charge and discharge test was performed at the same current density. The results are as follows: Fig.10 As shown in the figure, after 30 cycles, the capacity increased from 2461.6 mAh g -1 Rapidly decays to 580.1 mAh g -1 This is attributed to the agglomeration of Si@C nanoparticles due to the surface effect brought about by lithium ion insertion / deintercalation, which limits the continuous insertion / deintercalation of lithium ions.

[0052] Comparative Example 4

[0053] The Si particles in step 1) of Example 1 were directly assembled into a lithium-ion battery according to steps 1) to 3) of Example 2, and a charge and discharge test was performed at the same current density. The results are as follows: Fig.11 As shown, the battery is at 0.1A g -1 After only two cycles at a current density of 2511.3 mAh g -1 Rapidly decays to 710.4 mAh g -1 , and the charge and discharge test could not be performed during the subsequent charge and discharge process. The rapid failure of the electrode is attributed to the fact that a large amount of irreversibly embedded lithium ions caused the silicon particle structure to expand rapidly, resulting in poor contact between the electrode material and the current collector. In addition, the SEI film that continues to thicken on the surface of the silicon particles further hinders the insertion / deinsertion of lithium ions.

[0054] The present invention improves the conductivity of the silicon negative electrode by wrapping a layer of amorphous carbon on the surface of silicon particles, and at the same time prevents excessive lithium ion embedding from causing surface passivation or structural collapse of the silicon negative electrode. Then, the prepared silicon@carbon nanocomposite material is embedded in the three-dimensional framework structure of the gel electrolyte by a sol-gel method, and then carbonized in one step to obtain silicon@carbon / carbon. Compared with pure silicon particles and silicon@carbon nanocomposites, the porous framework structure can absorb electrolyte, increase the silicon-electrolyte contact area, and thus improve the electron / ion transmission kinetics. In addition, anchoring the silicon@carbon nanoparticles on the porous three-dimensional framework can also prevent the nanostructured silicon particles from agglomerating, and at the same time provide a large amount of space, alleviate the drastic volume change of the silicon negative electrode during the charge and discharge process, and prevent the silicon negative electrode from falling off the current collector. The prepared lithium-ion battery has the advantages of good cycle performance, high energy density, non-toxicity and pollution-free.

[0055] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a Si@C / C nanocomposite material, characterized in that: The preparation method comprises the following steps: 1) dispersing silicon particles in water, then adding tris(hydroxymethyl)aminomethane, hydrochloric acid and dopamine hydrochloride under stirring, stirring, centrifuging, washing and drying; and then calcining in an inert atmosphere to obtain a Si@C composite material; 2) dispersing the Si@C composite material in water, adding acrylamide monomer and N,N-methylenebisacrylamide crosslinking agent, dissolving under stirring at room temperature, adding a photoinitiator and mixing evenly, and forming a gel by ultraviolet light irradiation; 3) The obtained gel is immersed in liquid nitrogen and freeze-dried to obtain a precursor, which is then calcined in an inert atmosphere to obtain a Si@C / C nanocomposite material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon particles to water in step 1) is 1:5000 to 1:

50.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of trihydroxyaminomethane to water in step 1) is 1:100 to 4:5, and the concentration of the hydrochloric acid solution is 12 mol L -1 , the volume ratio of dopamine hydrochloride to water is 1:500~2:5, and the mass ratio of dopamine hydrochloride to water is 1:10000~1:

10.

4. The preparation method according to claim 1 or 2, characterized in that: In step 1), the stirring time is 0.5 to 120 hours; the inert atmosphere is argon; the calcination temperature is 300 to 800° C. and the calcination time is 0.5 to 12 hours.

5. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of the Si@C composite material to deionized water is 1:5000-1:50, the mass ratio of the acrylamide monomer to deionized water is 1:50-9:10, and the mass ratio of the N,N-methylenebisacrylamide crosslinking agent to deionized water is 1:20000-1:

200.

6. The preparation method according to claim 1 or 5, characterized in that: In step 2), the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the volume ratio of the photoinitiator to deionized water is 1:5000 to 1:

10.

7. The preparation method according to claim 1 or 5, characterized in that: In step 2), the ultraviolet light irradiation time is 5 to 6400 s.

8. The preparation method according to claim 1, characterized in that: In step 3), the freeze-drying time is 0.5 to 96 hours; the inert atmosphere is argon, the calcination temperature is 300 to 800° C., and the calcination time is 0.5 to 12 hours.

9. A Si@C / C nanocomposite material prepared by the preparation method according to any one of claims 1 to 8.

10. A high performance lithium ion battery, characterized in that: It is prepared using the Si@C / C nanocomposite material described in claim 9.

Citation Information

Patent Citations

  • Preparation method of silicon-based anode material for lithium ion battery

    CN105226260A

  • Omposition for preparing silicon-carbon composite, silicon-carbon composite, electrode for secondary battery comprising same, and method for producing silicon-carbon composite

    CN106252615A

  • SiC-based composite ceramic and preparation method thereof

    CN106747455A

  • Electrode of silicon based negative electrode active material, method for producing same, and lithium secondary battery comprising same

    KR1020140046496A